"Extremely Stupid Guidelines": On The Development of Historical Questions Around Guru Tegh Bahadur’s Martyrdom - Judge, Rajbir Singh (Journal of the American Academy of Religion, 2024)
In 1675, Mughal authorities beheaded Guru Tegh Bahadur, the ninth Sikh Guru and, today, the martyrdom has become a highly contested historical question within scholarly circles. This article investigates the emergence of the event as a historical question and how the emphasis of historical fact-finding refashioned scholarly approaches to the Sikh tradition in the colonial and postcolonial periods. I end by exploring how the famous Sikh intellectual and politician, Sirdar Kapur Singh (1909-1986), drew upon the Sikh tradition to challenge the very premises of such historiographical framing in his landmark essay, "Who Killed Guru Tegh Bahadur?" and the limits to his challenge. I ask: What do we make of Kapur Singh’s frustration and disgust at the history writing that came to dominate the Sikh tradition? I show how Kapur Singh does not transcend the epistemological constraints of history through a better or more accurate rendition of the past. Instead, he disrupts the historiographical operation in his frustration with history writing and what he calls its "extremely stupid guidelines."